Leadership Training Guna Membangun Jiwa Kepemimpinan bagi Guru di Sekolah Dasar Islam - M. Zuhnir Piliang; Abdul Rahman Alfarasyi; Mutia Meireni; Hayatul Khairul Rahmat; Irma Sianipar; Muthi’ah Alfiyah Yamin (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2023)
Leadership Training for teachers in elementary schools aims to build a spirit of leadership for teachers at SDIT Nuur A'laa Nuur Tambun Bekasi and increase teacher productivity at SDIT Nuur A'laa Nuur Tambun Bekasi. This community service activity is carried out at SDIT Nuur A'laa Nuur Tambun Bekasi, which is located at Jalan Buwek Raya No. 2B Sumber Jaya Tambun Selatan, Bekasi. This training was carried out using the method of exposure and discussion. Through this training, teachers at SDIT Nuur A'laa Nuur Tambun Bekasi are expected to be leaders who inspire to do something new and advance school organizations.